The Principle of Nebis In Idem in Settlement of Civil Cases in Indonesia - Nahdhah, Nahdhah (International Journal of Law, Environment, and Natural Resources, 2022)
The principle of Nebis in Idem in its application in Indonesia is a fundamental principle because it is related to the requirements of a case claim which this principle can determine whether or not a case may be tried. The mutual lawsuit that was carried out between MS GLOW and PS GLOW is fascinating because there are allegations of filing the same case. The method used in this research is normative research with a case approach based on Medan and Surabaya court decisions. The results of this study are the application of the Nebis In Idem Principle in Indonesia, especially in the MS Glow and PS Glow; in this case, the Medan Commercial Court has yet to decide on the same case. Therefore, the principle of nebis in idem did not apply in this case when it was taken to the Surabaya Commercial Court because the elements in the demands of Article 1917 of the Civil Code were not fulfilled. The legal consequence of the Nebis in Idem principle's enactment is that cases included in these conditions cannot be reclaimed, and these conditions apply cumulatively.